Generation and Transport of Dielectric Droplets along Microchannels by Corona Discharge - Qiang Tang; Shangru Zhou; Ruiheng Hu; Huai Zheng; Junheng Pan; Jau Tang (Micromachines, 2020)
In this paper, a phenomenon of generation and transport of droplets is proposed, which is based on the dielectric liquid electroconvection induced by corona discharge. We placed the dielectric fluid on a conductive/nonconductive substrate, and then it broke apart to become many small droplets that move along the conductive microchannel. The behaviors of dielectric droplets were experimentally observed on different conductive microchannels in details. Spreading speeds and sizes of dielectric droplets were analyzed at different driving voltages and conductive microchannels. This work highlights a simple approach to produce and manipulate dielectric droplets along microchannels.